(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Cooperative behaviors can be investigated in view of third-party sanctions. Altruistic punishment occurs when an individual chooses to suffer injury to punish the deserting behavior of another one. This study aimed to investigate whether cultural consequences in the Game of Altruistic Punishment select different patterns of punitive behavior. Participants were 20 children between 9 and 11. An ABCBAC reversal design was programmed to all Experiments. In Condition A, there were no points. In Condition B, participants received points by punishing equal distributions and not punishing unequal, and in Condition C by punishing unequal distributions and not punishing equals. Verbal reports were analyzed. The results showed control of cultural consequences over culturants in Conditions B and C. In addition, changes in Conditions occurred, in general, based on the performance criterion. As for verbal reports, a strong relationship between communication and cooperation among participants was observed.